2020
DOI: 10.3390/s20102956
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Broadband Tissue-Equivalent Liquid for SAR Measurement and Monitoring of Its Dielectric Properties for Use in a Sealed Phantom

Abstract: We report on the development of a method for measuring the permittivity and conductivity of fluids inside a sealed tank (or a pipe) by using an embedded coaxial probe. Permittivity and conductivity in the frequency range 600 MHz to 6 GHz are determined from measurements of a complex reflection coefficient by using a vector network analyser (VNA) that is connected to the embedded probe via a coaxial cable. Substitution methods for calibration of an inaccessible probe are studied in this paper. These require the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The obtained E-filed values are measured by using the proposed design, and after comparison of Tables 3 and 4, the obtained SAR values are within the standard limits. As per IEC-62209-1,2,3/IEEE 1528 [25–27], the circular probe array each source of uncertainty budget evaluation has been performed as shown in Table 5. Soh et al .…”
Section: Measurement Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained E-filed values are measured by using the proposed design, and after comparison of Tables 3 and 4, the obtained SAR values are within the standard limits. As per IEC-62209-1,2,3/IEEE 1528 [25–27], the circular probe array each source of uncertainty budget evaluation has been performed as shown in Table 5. Soh et al .…”
Section: Measurement Discussionmentioning
confidence: 99%
“…The obtained E-filed values are measured by using the proposed design, and after comparison of Tables 3 and 4, the obtained SAR values are within the standard limits. As per IEC-62209-1,2,3/IEEE 1528 [25][26][27], the circular probe array each source of uncertainty budget evaluation has been performed as shown in Table 5. Soh et al have reported a SAR value of 0.54 W/kg in reference [28], but the proposed work obtained a SAR value of 0.24 W/kg; the difference may vary due to the repeatability of the test.…”
Section: Measurement Discussionmentioning
confidence: 99%